2011
DOI: 10.1021/am200350z
|View full text |Cite
|
Sign up to set email alerts
|

Surface Deposition and Phase Behavior of Oppositely Charged Polyion–Surfactant Ion Complexes. Delivery of Silicone Oil Emulsions to Hydrophobic and Hydrophilic Surfaces

Abstract: The adsorption from mixed polyelectrolyte–surfactant solutions at hydrophobized silica surfaces was investigated by in situ null-ellipsometry, and compared to similar measurements for hydrophilic silica surfaces. Three synthetic cationic copolymers of varying hydrophobicity and one cationic hydroxyethyl cellulose were compared in mixtures with the anionic surfactant sodium dodecylsulfate (SDS) in the absence or presence of a dilute silicone oil emulsion. The adsorption behavior was mapped while stepwise increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…The congruence between the visual phase behavior visual study and f-potential measurements enables deducing that PE-surfactant coacervation is the dominant mechanism for the emulsion flocculation. These observations and this deduction are consistent with literature reports for PE interactions with surfactants on flat surfaces in aqueous solution, where the bulk phase separation is found to control the interfacial adsorption [5,12,[16][17][18][19][20]. The phase behavior and fpotential measurements are schematically summarized as follows: as PE is added to initially stable anionic emulsion droplets, the electrostatic interaction of the oppositely charged PE and anionic surfactant results in coacervation and encapsulation/aggregation of the emulsion droplets and phase separation.…”
Section: Phase Behaviorsupporting
confidence: 90%
See 2 more Smart Citations
“…The congruence between the visual phase behavior visual study and f-potential measurements enables deducing that PE-surfactant coacervation is the dominant mechanism for the emulsion flocculation. These observations and this deduction are consistent with literature reports for PE interactions with surfactants on flat surfaces in aqueous solution, where the bulk phase separation is found to control the interfacial adsorption [5,12,[16][17][18][19][20]. The phase behavior and fpotential measurements are schematically summarized as follows: as PE is added to initially stable anionic emulsion droplets, the electrostatic interaction of the oppositely charged PE and anionic surfactant results in coacervation and encapsulation/aggregation of the emulsion droplets and phase separation.…”
Section: Phase Behaviorsupporting
confidence: 90%
“…A decrease in solubility (e.g., the formation of gel-like polymer-surfactant complexes, PSCs) drives the adsorption to a surface. The work of Nylander et al and Linse and Kallrot [5,12,[16][17][18][19][20][21][22] has contributed significantly to the experimental and theoretical investigations of the PE adsorption behavior onto a silica substrate in the presence or absence of anionic surfactants. In most of their studies, the surfactant is depleted from the surface due to non-favorable electrostatic repulsion; consequently coacervate complexes preferentially form in the bulk solution before interacting with the surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PS complex and resultant attractive interaction is influenced by many factors including surfactant concentration, added electrolytes, polymer backbone flexibility, polymer charge, and surfactant-polymer associations (often based on charge or hydrophobic interaction). This sensitivity and flexibility is one of the reasons why PS complexes are used so widely in formulated products (40). This has led to an extensive understanding of PS complex behaviour in the bulk (25,37,39,41).…”
Section: Introductionmentioning
confidence: 99%
“…9−12 Another protocol used to deposit films from mixed polymer−surfactant solutions is "coacervation by dilution", commonly employed in hair care applications. 2,13 The drawback with the latter technique is again that quite thin surface layers are typically produced, especially at high dilution of the solution. 13 A new approach to producing CS films on solid substrates was introduced by Antonietti et al 14,15 and Thunemann et al, 16 who showed that it was possible to cast CS films from certain organic solvents.…”
Section: Introductionmentioning
confidence: 99%